Crecimiento económico y su influencia en las importaciones en Loreto periodo 2018 – 2022 - Mejia Villacorta, Anthony Geraldo (2025)
This study aims to examine the impact of economic growth on imports in the Loreto region between the years 2018 and 2022. A descriptive-correlational approach was applied, with a non-experimental design, based on the collection of secondary data obtained from sources such as the National Superintendency of Customs and Tax Administration (SUNAT) and the Central Reserve Bank of Peru (BCRP). The results revealed that, throughout the analyzed period, the economic growth of Loreto, measured through the Gross Domestic Product (GDP), did not significantly influence total imports. Although GDP showed an increase, no significant correlation was found with the import of consumer goods, intermediate goods or capital goods. These results suggest that there are other factors that are influencing the behavior of imports in the region, beyond economic growth. The conclusions of the analysis indicate that Loreto's economic growth has not been a key element in the evolution of imports during the period examined. Broader research that includes additional factors, such as foreign investment, trade policies, and infrastructure development, is recommended to gain a more complete understanding of import dynamics in the region.